Pembelajaran Metode Cooperative Learning Mata Pelajaran IPS pada Siswa SMP Tunas Harapan Jaya - Lengsi Manurung (Jurnal Ilmiah Wahana Pendidikan, 2020)
The purpose of this study was to determine the effectiveness of the Cooperative Larning (CL) method on social studies subject junior high school students. The method used is a classroom action research method, with 2 cycles. The object of research is the students of SMP Tunas Harapan Jaya, Bekasi City. Respondents were 30 students of class VII. The first and second cycles were carried out using the cooperative learning (CL) method. The results showed that the average values ​​of the first cycle were 65.5. The second cycle is 77 . There is an increase of 12.5 points. This indicates that the cooperative method is effective in increasing student learning outcomes in social studies subjects in class VII SMP Tunas Harapan Jaya Bekasi. Students are more creative and seem to collaborate between students. Suggestions that can be conveyed are, so that teachers can use methods that are effective and suitable for students. It is hoped that children's learning patterns will be better and not boring.